Drivers and constraints in an emerging rural biogas system: actors’ perceptions from Northern Savonia - Aro, Kalle; Kojo, Matti; Rikkonen, Pasi; Rasi, Saija (Springer Nature, 2025)
Background The biogas niche is usually approached from a top-down perspective, and its actors are considered a unanimous advocacy group in the national policy discourse. This setting downplays the diversity of actors and their opinions at a subnational level. In this study, ten biogas actors from the farm-level, industry, regional administration, and potential end-users in the Finnish region of Northern Savonia were interviewed. The actors’ perceptions of the national and regional biogas sectors were explored. Results The national biogas policy framework appears discontinuous, and statements regarding biogas targets are perceived as ambiguous, thus lacking creditability at a local level. The economic feasibility of rural biogas production places a strong boundary condition for the local biogas system. When moving from the national to a local level, individual actor’s perception of the optimal value chain becomes highlighted. Extending the actor network beyond the regional context was deemed vital for the long-term stability of the locally emergent biogas ecosystem. As municipalities can influence both production and consumption domains, they were called to play a more active role in constructing local biogas systems. Conclusions The results of this study provided three insights: (1) social, political, and environmental drivers influence the biogas sector in addition to techno-economic drivers; (2) drivers and constraints are perceived differently by actors in agricultural biogas production than by actors in distribution and end-use; and (3) the local biogas niche contains partly divergent perceptions of how the biogas system should be organised. Connecting actors early through joint planning and formulating case-by-case business models may help mediate any conflicts of interest.
Keywords: rural biogas system; rural development; active interviews; qualitative content analysis; Finland; case study